Effect Of Multifaceted Intervention On Knowledge, Attitude, Iron Intake, Hemoglobin (Hb) Levels In Adolescent Women With Mild To Moderate Anemia At Senior High School 2 Tomia Of Wakatobi Regency - Unjar Zakiyah, May Sri; Nasir, Sudirman; Syafar, Muhammad; Azzahra, Yudhira (Journal of Neonatal Surgery, 2025)
Background. According to WHO in 2021, the prevalence of anemia in the world was around 29.9%, there were 46 cases of mild to moderate anemia or 21.8% in adolescent girls at Senior High School 2 Tomia, this figure is quite high considering that the provision of Iron Tablet supplementation is carried out routinely. This program has not achieved the target of reducing anemia in adolescents because there is no evaluation and follow-up after the Iron Tablet supplementation has given, lack of knowledge of students and no school and parental control are the contributing factors. Aims. to analyze the effect of multifaceted intervention on knowledge, attitudes, iron intake and hemoglobin (Hb) levels in adolescent girls with mild to moderate anemia. Method.The type of quasi-experimental study with a design one group pretest and posttest design with a sample of 43 respondents. This study was conducted at SMAN 2 Tomia. from September to November 2024. Results. This study shows that multifaceted intervention has a significant effect on knowledge about anemia and nutrition of young women with mild to moderate anemia (p value = 0.000), attitudes about anemia and nutrition teenager daughter mild anemia moderate (p value=0.000), intake substance iron teenager daughter mild anemia moderate (p value=0.000), hemoglobin (Hb) levels in adolescents daughter mild anemia moderate (p value=0.000). Conclusion: The multifaceted intervention statistical test have an effect real to hemoglobin (Hb) levels in adolescents daughter mild anemia is at SMAN 2 Tomia with a p value = 0.000 (p < 0.05).